Impact of Planting Windows on Growth, Yield and Economics of Potato Production under Climate Change Scenario in Central India - Singh, S. P. (International Journal of Bio-resource and Stress Management, 2016)
A field experiment was conducted to study adaptation of potato to climate aberrations at Central Potato Research Station, Gwalior, India which is located in Central Plains of India. Potato cultivar Kufri Jyoti was planted with five planting windows (planting dates) viz 15th September, 30th September, 15th October, 30th October and 15th November for two consecutive years during 2009−10 and 2010−11. Treatments were replicated four times. Early planting at higher temperature delayed tuberization, reduced tuber number (1,80,399) and finally there was drastic reduction in tuber yields (11.4 t ha-1). Highest tuber yield (31.6 t ha-1) was recorded with 15th October planted crop which was significantly higher over early planting windows. Net returns were negative in 15th and 30th September planting windows due to reduction in tuber yields. Highest N uptake (92 kg ha-1) was recorded with 15th October planted crop however it was lowest with 15th September planted crop. Highest water use efficiency (126 kg tuber/mm-1 water) was also recorded with the same treatment because of higher tuber yield and lesser evapo-transpiration demand during crop growth period. Delayed planting of 15th November also reduced tuber yield due to increased temperature at the active bulking period of the potato. Thus, 15th October planting window is most suitable date for planting ware potato crop for the region to get good yield, net returns and increase input use efficiency.